Compound as well as preparation method and application thereof
The new compound prepared by reacting triethanolamine and vinylamine in the presence of catalyst and hydrogen has solved the problems of poor anti-swelling effect, poor washing properties and low temperature resistance of existing clay anti-swelling agents, and achieved efficient clay anti-swelling and high-temperature resistance.
Patent Information
- Application Number
- CN202311285954.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-07
AI Technical Summary
The existing clay anti-swelling agent has poor anti-swelling effect, poor water washing and low temperature resistance, which cannot effectively solve the problem of pore and throat blockage caused by the hydration and expansion of water-sensitive minerals during the oil field development process.
A novel compound is provided with a structure containing a plurality of amine groups, which is prepared by reacting triethanolamine and vinylamine in the presence of a catalyst and hydrogen. This compound has multi-point adsorption capability, can effectively adsorb on the surface of clay, improves flush resistance and anti-swelling properties, and remains stable at high temperatures.
When used as a clay anti-swelling agent, this compound has good anti-swelling properties, water washing resistance and high temperature resistance, which can effectively prevent clay particles from moving and improve the oil field development effect.
Smart Images

Figure CN119775149A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil production engineering, and in particular to a compound and a preparation method and application thereof. Background Art
[0002] Clay is a common mineral in formation rocks. Clay has the characteristic of swelling when it comes into contact with water. Therefore, during the process of reservoir development such as water injection, acidification or fracturing in oil fields, the voids in clay-rich reservoirs will be reduced due to clay swelling, and the pores will be blocked in large quantities, causing water-sensitive damage. In order to reduce this reservoir damage, clay anti-swelling agents are widely used. Clay anti-swelling agents can effectively adsorb on the surface of clay to prevent water-sensitive minerals in the reservoir from hydrating, swelling and dispersing and migrating, thereby damaging the oil and gas layers and affecting the effect of oil field development.
[0003] The commonly used anti-swelling agents include inorganic salts, cationic polymers and quaternary ammonium salts. Inorganic salts are the earliest used clay anti-swelling agents, mainly using inorganic salt ions such as K + Embedded in the clay crystal structure to neutralize the electronegativity of the clay, but inorganic salt clay anti-swelling agents have weak bonding with the formation and poor anti-clay migration ability. Cationic polymer molecules contain multiple positive charges and can be adsorbed at multiple points on the surface of clay minerals. They have good anti-swelling effects and are resistant to erosion, but they have large molecular weights and are easy to block the pore throats of formations, harming the permeability of formations, and are not suitable for dense formations. On the other hand, cationic polymers have poor temperature resistance and are prone to decomposition at high temperatures, which makes their anti-swelling effects disappear. Although quaternary ammonium salts have small molecular weights and will not clog the formations themselves, they can only produce single-point adsorption on the clay surface, so their anti-swelling effects are not as good as cationic polymers.
[0004] Existing anti-swelling agents have too few adsorption sites, poor anti-swelling effects, and too large molecular weight, which makes them inapplicable to low permeability formations. They also have poor molecular stability and are prone to chain breakage at high temperatures, so their temperature resistance is low. Therefore, it is necessary to develop a clay anti-swelling agent with good anti-swelling properties, water washability, and temperature resistance. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor anti-swelling effect, poor water washability and low temperature resistance of the anti-swelling agent in the prior art, and to provide a compound and its preparation method and application.
[0006] In order to achieve the above object, the first aspect of the present invention provides a compound, wherein the compound has a structure shown in formula (1),
[0007]
[0008] Among them, n1, n2, and n3 are each independently a natural number from 0 to 4.
[0009] The second aspect of the present invention provides a method for preparing a compound, which comprises: reacting triethanolamine and ethyleneamine in the presence of a catalyst and hydrogen to obtain the compound.
[0010] The third aspect of the present invention provides a compound obtained by the preparation method.
[0011] The fourth aspect of the present invention provides a use of the compound in a clay anti-swelling agent.
[0012] Through the above technical scheme, the present invention provides a compound and its preparation method and application. When the compound is used as a clay anti-swelling agent, it has moderate molecules and multiple adsorption points, and has the advantages of strong bonding with the formation, high water washability, good anti-swelling performance, good effect in preventing clay particle migration and high temperature resistance. DETAILED DESCRIPTION
[0013] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0014] The first aspect of the present invention provides a compound, wherein the compound has a structure shown in formula (1),
[0015]
[0016] Among them, n1, n2, and n3 are each independently a natural number from 0 to 4.
[0017] In the present invention, the molecular structure of the compound contains multiple amine groups, and the number of amine groups is large. Ionization occurs in the aqueous solution to form amine cations with high charge density, which can greatly reduce the electronegativity of the clay and inhibit the hydration and dispersion of the clay; the multi-point adsorption formed by the amine groups enables it to be firmly adsorbed on the surface of the clay, improving its anti-scouring property. More preferably, n1, n2, and n3 are the same. Among them, when n1=n2=n3=0, the ethyleneamine is selected from ethylenediamine; when n1=n2=n3=1, the ethyleneamine is selected from diethylenetriamine; when n1=n2=n3=2, the ethyleneamine is selected from triethylenetetramine; the ethyleneamine is selected from diethylenetriamine; when n1=n2=n3=3, the ethyleneamine is selected from tetraethylenepentamine; the ethyleneamine is selected from diethylenetriamine; when n1=n2=n3=4, the ethyleneamine is selected from pentaethylenehexamine. Preferably, n1, n2, and n3 are each independently an integer of 1-3. When the compound is used as a clay anti-swelling agent, it has a moderate molecule and many adsorption sites, and has the advantages of strong bonding with the formation, high water resistance, good anti-swelling performance, good effect in preventing clay particle migration, and high temperature resistance.
[0018] The composition and structure of the compound can be determined by NMR, IR, GPC, elemental analysis, etc., or by preparing and feeding.
[0019] The second aspect of the present invention provides a method for preparing a compound, which comprises: reacting triethanolamine and ethyleneamine in the presence of a catalyst and hydrogen to obtain the compound.
[0020] In the present invention, the compound is prepared by amination reaction with triethanolamine, ethyleneamine and hydrogen as raw materials in the presence of a supported solid catalyst.
[0021] The present invention prepares the compound through a one-step reaction, has fewer reaction steps, a simple process flow, and is easy for industrial production; no organic solvent is used, three wastes are less, and is beneficial to environmental protection.
[0022] In the present invention, during the reaction, under the action of a catalyst and in a hydrogen atmosphere, triethanolamine is first dehydrogenated to convert a hydroxyl group into an aldehyde group, and then the aldehyde group reacts with an amine group in vinylamine to produce an imine, and the generated imine is then hydrogenated to produce an amine, thereby obtaining the compound. The amine value of the compound can be analyzed by a titration method to determine the degree of reaction, and its structure can be analyzed by infrared spectroscopy.
[0023] In some specific embodiments of the present invention, the ethyleneamine is selected from one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine, preferably one or more of diethylenetriamine, triethylenetetramine and tetraethylenepentamine.
[0024] In some specific embodiments of the present invention, the molar ratio of triethanolamine to ethyleneamine is 1:3-6, and the amount of the catalyst is 1-5 wt % of the total amount of triethanolamine and ethyleneamine.
[0025] In some specific embodiments of the present invention, the reaction temperature is 160-220° C., the reaction hydrogen partial pressure is 1-2.5 MPa, and the reaction time is 4-8 hours. The temperature, time, and hydrogen partial pressure of the reaction are limited to the above ranges, so that the reaction of triethanolamine and ethyleneamine can be more complete, and no side reactions are generated, thereby achieving a better catalytic effect.
[0026] In some specific embodiments of the present invention, the catalyst comprises a main active component, an auxiliary agent and a carrier, wherein the carrier is selected from silicon dioxide and / or aluminum oxide, the main active component is Ni and Cu, and the auxiliary agent is Cr and Mo. The main active component and the auxiliary agent are loaded on the carrier.
[0027] In some specific embodiments of the present invention, based on the total weight of the catalyst, the content of Ni in the catalyst is 20-40wt%, the content of Cu is 4-8wt%, the content of Cr is 1-3wt%, the content of Mo is 0.5-1.5wt%, and the content of the carrier is 47.5-74.5%. The catalyst components defined in the above range have better catalytic effects, can react triethanolamine and ethyleneamine more completely, and can control no side reactions, thereby achieving better catalytic effects.
[0028] The third aspect of the present invention provides a compound obtained by the preparation method.
[0029] In the present invention, the composition and structure of the compound can be determined by nuclear magnetic resonance, infrared, elemental analysis, etc., or by preparing and feeding.
[0030] The fourth aspect of the present invention provides a use of the compound in a clay anti-swelling agent.
[0031] In some specific embodiments of the present invention, the room temperature anti-swelling rate of the clay anti-swelling agent at a dosage of 0.5 wt% is ≥90%, the water washing resistance is ≥95%, and the temperature resistance is ≥350°C.
[0032] In the present invention, the clay anti-swelling agent has a moderate molecular weight, will not cause blockage to low-permeability formations, and has a good oil recovery effect.
[0033] The present invention will be described in detail below through examples.
[0034] Referring to "SY / T5971-2016 Performance Evaluation Method of Clay Anti-Swelling Agent for Water Injection", the anti-swelling rate and water washability of the clay anti-swelling agent were tested.
[0035] High temperature anti-swelling rate test method: add 3.00g sodium bentonite to 60mL of clay anti-swelling agent solution with a mass concentration of 1%, shake well and mix, and then put it into an aging kettle; then put it into a high temperature aging furnace and age it at a set temperature for 24 hours; after cooling to room temperature, transfer all the clay anti-swelling agent solution in the aging kettle into a 100mL beaker, shake well, quickly take out 10mL and add it to a centrifuge tube, put it into a centrifuge with automatic balancing function, centrifuge it at 1500r / min for 15 minutes, and read the expansion volume V1 of the bentonite. The high temperature anti-swelling rate calculation formula is shown in Formula 3.
[0036]
[0037] Where: F—high temperature anti-expansion rate, %;
[0038] V0—volume of sodium bentonite in kerosene, mL;
[0039] V1—volume of sodium bentonite in clay anti-swelling agent, mL;
[0040] V2—Volume of sodium bentonite in clean water, mL.
[0041] The compound purity test adopts the triethanolamine conversion rate test method:
[0042] Weigh 1 g of the separated product into a conical flask, then add it to 50 mL of a pyridine solution containing phthalic anhydride, wherein the mass ratio of phthalic anhydride to pyridine is 20:120, and react at 115°C under reflux conditions for 1 hour. After cooling, titrate the excess phthalic anhydride with 0.5 mol / L sodium hydroxide solution, and at the same time, perform a blank experiment with 50 mL of a pyridine solution containing phthalic anhydride. The calculation formula for the hydroxyl content of the product is shown in Formula 1, and the calculation formula for the triethanolamine conversion rate is shown in Formula 2.
[0043] S = C*(V0-V1) / m Formula 1;
[0044] S: Hydroxyl content, mmol / g
[0045] C: sodium hydroxide concentration, mol / L;
[0046] V0: volume of sodium hydroxide consumed by blank sample, mL;
[0047] V1: Volume of sodium hydroxide consumed by the sample, mL;
[0048] m: sample mass;
[0049] Triethanolamine conversion rate X% = (20.13-S)*100 / 20.13 Formula 2;
[0050] 20.13: Hydroxyl content in triethanolamine, mmol / g.
[0051] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be obtained through commercial channels. The composition and structure of the compounds described in the following examples can be determined by preparing the raw materials.
[0052] Example 1
[0053] 37.25g triethanolamine, 77.25g diethylenetriamine and 4.58g supported solid catalyst (20% Ni, 8% Cu, 3% Cr, 1% Mo, silicon dioxide as carrier) were weighed and added to the reactor. 8-10MPa nitrogen was filled into the magnetic high-pressure reactor. Foam water was used to check whether there was leakage. After standing for 30 minutes, the pressure did not drop. Then, 0.5MPa nitrogen was used to replace it 3 times, and then 0.5MPa hydrogen was used to replace it 2 times. 1MPa hydrogen was introduced, and the temperature was slowly raised to 180°C under stirring at a speed of 800rpm, and the reaction was carried out for 6h. After the reaction was completed, cooling water was passed to cool down. When the temperature dropped to 60°C, the gas was slowly exhausted, and the gas was absorbed by water and discharged. The catalyst and the reaction product were separated by hot filtration, and the unreacted raw materials were removed by reduced pressure distillation to obtain compound S1, and the purity of S1 was 100%. Compound S1 has the structure shown in formula (1), and n1=n2=n3=1.
[0054] Example 2
[0055] Weigh 37.25g triethanolamine, 164.25g triethylenetetramine and 3.67g supported solid catalyst (30% Ni, 6% Cu, 2% Cr, 0.5% Mo, aluminum oxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 1.5MPa hydrogen, stir at a speed of 600rpm, slowly heat up to 200℃, and react for 8h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, and remove the unreacted raw materials by vacuum distillation to obtain compound S2, the purity of S2 is 100%. Compound S2 has a structure represented by formula (1), and n1=n2=n3=2.
[0056] Example 3
[0057] Weigh 37.25g triethanolamine, 189g tetraethylenepentamine and 11.31g supported solid catalyst (25% Ni, 7% Cu, 1% Cr, 1.5% Mo, aluminum oxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 2.5MPa hydrogen, stir at a speed of 700rpm, slowly heat to 210℃, and react for 7h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, and remove the unreacted raw materials by vacuum distillation to obtain compound S3, the purity of S3 is 100%. Compound S3 has the structure represented by formula (1), and n1=n2=n3=3.
[0058] Example 4
[0059] 37.25g triethanolamine, 290g pentaethylenehexamine and 6.55g supported solid catalyst (35% Ni, 5% Cu, 2% Cr, 1% Mo, silicon dioxide as carrier) were weighed and added to the reactor. 8-10MPa nitrogen was filled into the magnetic high-pressure reactor. Foam water was used to check whether there was leakage. After standing for 30 minutes, the pressure did not drop. Then, 0.5MPa nitrogen was used to replace it 3 times, and then 0.5MPa hydrogen was used to replace it 2 times. 2MPa hydrogen was introduced, and the temperature was slowly raised to 220°C under stirring at a speed of 800rpm, and the reaction was carried out for 5h. After the reaction was completed, cooling water was passed to cool down. When the temperature dropped to 60°C, the gas was slowly exhausted, and the gas was absorbed by water and discharged. The catalyst and the reaction product were separated by hot filtration, and the unreacted raw materials were removed by reduced pressure distillation to obtain compound S4, and the purity of S4 was 100%. Compound S4 has the structure shown in formula (1), and n1=n2=n3=4.
[0060] Example 5
[0061] 37.25g triethanolamine, 75g ethylenediamine and 1.13g supported solid catalyst (40% Ni, 4% Cu, 1% Cr, 1.5% Mo, aluminum oxide as carrier) were weighed and added to the reactor. 8-10MPa nitrogen was filled into the magnetic high-pressure reactor. Foam water was used to check for leaks. After standing for 30 minutes, the pressure did not drop. Then, 0.5MPa nitrogen was used to replace the pressure three times, and then 0.5MPa hydrogen was used to replace the pressure twice. 2MPa hydrogen was introduced. Under stirring at a speed of 500rpm, the temperature was slowly raised to 220°C and the reaction was carried out for 4h. After the reaction was completed, cooling water was passed to cool the reaction. When the temperature dropped to 60°C, the gas was slowly exhausted. The gas was absorbed by water and the material was discharged. The catalyst and the reaction product were separated by hot filtration, and the unreacted raw materials were removed by reduced pressure distillation to obtain compound S5, and the purity of S5 was 100%. Compound S5 has the structure shown in formula (1), and n1=n2=n3=0.
[0062] Example 6
[0063] Weigh 37.25g triethanolamine, 60g ethylenediamine and 1.27g supported solid catalyst (35% Ni, 8% Cu, 2.5% Cr, 0.5% Mo, aluminum oxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 1.5MPa hydrogen, stir at a speed of 600rpm, slowly heat to 190℃, and react for 8h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, and remove the unreacted raw materials by vacuum distillation to obtain compound S5, the purity of S5 is 92.3%. Compound S5 has a structure represented by formula (1), and n1=n2=n3=0.
[0064] Example 7
[0065] Weigh 37.25g triethanolamine, 103g diethylenetriamine and 2.81g supported solid catalyst (35% Ni, 8% Cu, 2.5% Cr, 0.5% Mo, silicon dioxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 2MPa hydrogen, stir at 800rpm, slowly heat to 210℃, and react for 5h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, remove the unreacted raw materials by vacuum distillation, and obtain compound S1, the purity of S1 is 92.2%. Compound S1 has a structure represented by formula (1), and n1=n2=n3=1.
[0066] Example 8
[0067] Weigh 37.25g triethanolamine, 219g triethylenetetramine and 8.97g supported solid catalyst (35% Ni, 8% Cu, 2.5% Cr, 0.5% Mo, silicon dioxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 1.5MPa hydrogen, stir at 800rpm, slowly heat up to 220℃, and react for 6h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust, and the gas is absorbed by water to discharge. Filter and separate the catalyst and reaction product while hot, and remove the unreacted raw materials by vacuum distillation to obtain compound S2, the purity of S2 is 91.8%. Compound S2 has a structure represented by formula (1), and n1=n2=n3=2.
[0068] Example 9
[0069] Weigh 37.25g triethanolamine, 236.25g tetraethylenepentamine and 10.94g supported solid catalyst (35% Ni, 8% Cu, 2.5% Cr, 0.5% Mo, silicon dioxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 1MPa hydrogen, stir at a speed of 700rpm, slowly heat up to 200℃, and react for 8h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, and remove the unreacted raw materials by vacuum distillation to obtain compound S3, the purity of S3 is 93.1%. Compound S3 has the structure represented by formula (1), and n1=n2=n3=3.
[0070] Example 10
[0071] Weigh 37.25g triethanolamine, 174g pentaethylene hexamine and 10.56g supported solid catalyst (35% Ni, 8% Cu, 2.5% Cr, 0.5% Mo, aluminum oxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 2MPa hydrogen, stir at 800rpm, slowly heat to 180℃, and react for 7h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, remove the unreacted raw materials by vacuum distillation, and obtain compound S4, the purity of S4 is 91.2%. Compound S4 has the structure represented by formula (1), and n1=n2=n3=4.
[0072] Embodiment 11
[0073] Weigh 37.25g triethanolamine, 103g diethylenetriamine and 2.81g supported solid catalyst (15% Ni, 3% Cu, 7.5% Cr, 6.5% Mo, silicon dioxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 2MPa hydrogen, stir at 800rpm, slowly heat to 210℃, and react for 5h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, remove the unreacted raw materials by vacuum distillation, and obtain compound S1, the purity of S1 is 54.2%. Compound S1 has a structure represented by formula (1), and n1=n2=n3=1.
[0074] Example 12
[0075] Weigh 37.25g triethanolamine, 103g diethylenetriamine and 2.81g supported solid catalyst (35% Ni, 8% Cu, 2.5% Cr, 0.5% Mo, silicon dioxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 0.8MPa hydrogen, stir at 800rpm, slowly heat to 210℃, and react for 5h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, remove the unreacted raw materials by vacuum distillation, and obtain compound S1, the purity of S1 is 68.2%. Compound S1 has a structure represented by formula (1), and n1=n2=n3=1.
[0076] Example 13
[0077] Weigh 37.25g triethanolamine, 103g diethylenetriamine and 2.81g supported solid catalyst (35% Ni, 8% Cu, 2.5% Cr, 0.5% Mo, silicon dioxide as carrier) and add them to the reactor. Fill the magnetic high-pressure reactor with 8-10MPa nitrogen, check with foam water to see if there is any leakage, let it stand for 30min, and if the pressure does not drop, replace it with 0.5MPa nitrogen 3 times, and then replace it with 0.5MPa hydrogen 2 times, pass 3MPa hydrogen, stir at 800rpm, slowly heat to 210℃, and react for 5h. After the reaction is completed, cool it with cooling water, wait until the temperature drops to 60℃, slowly exhaust the gas, absorb the gas through water, and discharge the material. Filter and separate the catalyst and reaction product while hot, and remove the unreacted raw materials by vacuum distillation to obtain compound S1, the purity of S1 is 66.5%. Compound S1 has a structure represented by formula (1), and n1=n2=n3=1.
[0078] Comparative Example 1
[0079] Commercially available clay anti-swelling agent FP-HJZ.
[0080] Test Example 1:
[0081] The room temperature anti-swelling rate and water washing resistance after three water washings of the compounds with 100% purity obtained in Examples 1-5 as clay anti-swelling agents and the clay anti-swelling agent in Comparative Example 1 were tested, wherein the clay anti-swelling agent was a 0.5wt% aqueous solution.
[0082] The high temperature anti-swelling rates of the compounds with 100% purity obtained in Examples 1-5 as clay anti-swelling agents and the clay anti-swelling agent of Comparative Example 1 were tested, wherein the clay anti-swelling agent was a 1 wt % aqueous solution.
[0083] The results of room temperature anti-swelling rate, water washability rate and high temperature anti-swelling rate of Examples 1-5 and Comparative Example 1 are shown in Table 1.
[0084] Table 1
[0085]
[0086] It can be seen from the results in Table 1 that the clay anti-swelling agent prepared by the purified compound of the present invention, such as Examples 1-5, has multiple amine groups in the molecular structure and different types, which can be effectively adsorbed on the clay surface and well wrap the clay, so that it has good anti-swelling effect and temperature resistance, and its effect is better than the conventional clay anti-swelling agent of Comparative Example 1. By comparing Examples 1-5, it can be seen that the compounds of Examples 1-3 have better room temperature anti-swelling rate, water washing resistance rate and high temperature anti-swelling rate when used as clay anti-swelling agents, and the effect is better than that of Examples 4 and 5. The ethyleneamine is preferably one or more of diethylenetriamine, triethylenetetramine and tetraethylenepentamine. The obtained compound has better room temperature anti-swelling rate, water washing resistance rate and high temperature anti-swelling rate when used as a clay anti-swelling agent.
[0087] Test Example 2:
[0088] The room temperature anti-swelling rate and water washing resistance after three water washings of the reaction products with purity less than 100% obtained in Examples 6-13 and the clay anti-swelling agent of Comparative Example 1 were tested, wherein the clay anti-swelling agent was a 0.5wt% aqueous solution, to illustrate the effects of different reaction conditions and catalyst components on the reaction.
[0089] The high temperature anti-swelling rates of the reaction products obtained in Examples 6-13 as clay anti-swelling agents and the clay anti-swelling agent in Comparative Example 1 were tested, wherein the clay anti-swelling agent was a 1 wt% aqueous solution, to illustrate the effects of different reaction conditions and catalyst components on the reaction.
[0090] The results of room temperature anti-swelling rate, water washing resistance rate and high temperature anti-swelling rate of Examples 6-13 and Comparative Example 1 are shown in Table 2.
[0091] Table 2
[0092]
[0093] It can be seen from the results in Table 2 that the clay anti-swelling agent prepared by the present invention, such as Examples 6-13, has a plurality of amine groups of different types in its molecular structure, which can be effectively adsorbed on the clay surface and well wrap the clay, so that it has good anti-swelling effect and temperature resistance, and its effect is better than that of the conventional clay anti-swelling agent in Comparative Example 1.
[0094] By comparing Example 7 and Example 11, Example 7 has better room temperature anti-swelling rate, water washing resistance rate and high temperature anti-swelling rate than Example 11. When the catalyst component is within the component content range of the present invention, the catalytic effect is better, triethanolamine and ethyleneamine can be reacted more completely, no side reaction is controlled, and the product purity is higher. Therefore, when used as a clay anti-swelling agent, it has better room temperature anti-swelling rate, water washing resistance rate and high temperature anti-swelling rate.
[0095] By comparing Example 7 with Examples 12-13, Example 7 has better room temperature anti-swelling rate, water washing resistance rate and high temperature anti-swelling rate than Examples 12-13. The reaction of triethanolamine and ethyleneamine can be more complete within the hydrogen partial pressure range of the present invention, and no side reaction is controlled, thereby achieving a better catalytic effect and a higher product purity. Therefore, when used as a clay anti-swelling agent, it has better room temperature anti-swelling rate, water washing resistance rate and high temperature anti-swelling rate. When the hydrogen partial pressure is not within the range of the present application, the test results of the clay anti-swelling agent are poor.
[0096] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A compound, characterized in that The compound has a structure shown in formula (1), Among them, n1, n2, and n3 are each independently a natural number from 0 to 4.
2. A method for preparing a compound, characterized in that: include: The compound is obtained by reacting triethanolamine and ethyleneamine in the presence of a catalyst and hydrogen.
3. The preparation method according to claim 2, wherein The ethyleneamine is selected from one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.
4. The preparation method according to claim 2 or 3, wherein The molar ratio of triethanolamine to ethyleneamine is 1:3-6, and the amount of the catalyst is 1-5wt% of the total amount of triethanolamine and ethyleneamine.
5. The preparation method according to any one of claims 2 to 4, wherein: The reaction temperature is 160-220° C., the reaction hydrogen partial pressure is 1-2.5 MPa, and the reaction time is 4-8 h.
6. The preparation method according to any one of claims 2 to 5, wherein: The catalyst comprises a main active component, an auxiliary agent and a carrier, wherein the carrier is selected from silicon dioxide and / or aluminum oxide, the main active component is Ni and Cu, and the auxiliary agent is Cr and Mo.
7. The preparation method according to claim 6, wherein: Based on the total weight of the catalyst, the content of Ni in the catalyst is 20-40wt%, the content of Cu is 4-8wt%, the content of Cr is 1-3wt%, the content of Mo is 0.5-1.5wt%, and the content of the carrier is 47.5-74.5%.
8. A compound obtained by the preparation method according to any one of claims 2 to 7.
9. Use of the compound according to claim 1 or 8 as a clay anti-swelling agent.
10. The use according to claim 9, wherein: The room temperature anti-swelling rate of the clay anti-swelling agent at a dosage of 0.5wt% is ≥90%, the water washing resistance is ≥95%, and the temperature resistance is ≥350°C.
Citation Information
Patent Citations
Fast drilling fluid and preparation technique thereof
CN101186813A
Azimino compound used for trapping acid gas, and application thereof
CN102898313A
Anti-temperature clay anti-swelling agent and preparation method thereof
CN104099069A
Polycationic polysaccharide and application thereof
CN110903410A
Catalyst for synthesizing ethylene amine and method for preparing ethylene amine
WO2013152548A1